Estimating the creep strain to failure of PP at different load levels based on short term tests and Weibull characterization - L. M. Vas; P. Bakonyi (eXPRESS Polymer Letters)
The short and long term creep behavior is one of the most important properties of polymers used for engineering applications. In order to study this kind of behavior of PP tensile and short term creep measurements were performed and analyzed using long term creep behavior estimating method based on short term tensile and creep tests performed at room temperature, viscoelastic behavior, and variable transformations. Applying Weibull distribution based approximations for the measured curves predictions for the creep strain to failure depending on the creep load were determined and the parameters were found by fitting the measurements. The upper, mean, and lower estimations as well as the confidence interval for the means give a possibility for designers' calculations at arbitrary creep load levels.